Performance Analysis of Indonesia’s Mining Sector Price Index - Hastra Reza Satyatama; riwi sumantyo (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
Subprime mortage’s crisis in United States 2008 giving effect to the global capital markets especially the stock price index of the mining sector Indonesia. This research analyzes the effect of BI Rate, exchange rate, world gold price, crude oil price, and Dow Jones Industrial Average on the stock price index of the mining sector. This research employs time series monthly data of 2009-2016 with Error Correction Model-Engle Granger (ECM-EG) as the method. The analysis showed that the BI rate, exchange rate and world gold price, has a negative and significant effect. World oil prices affect positively but not significant meanwhile the Dow Jones Industrial Average has a positive and significant impact on the stock price index of the mining sector. For investors in the mining sector, should pay attention to the exchange rate of the rupiah and Dow Jones Index significantly in the mining sector of the stock price index.DOI: 10.15408/sjie.v6i2.5395